1988
DOI: 10.1037/0096-1523.14.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Examination of perceptual reorganization for nonnative speech contrasts: Zulu click discrimination by English-speaking adults and infants.

Abstract: The language environment modifies the speech perception abilities found in early development. In particular, adults have difficulty perceiving many nonnative contrasts that young infants discriminate. The underlying perceptual reorganization apparently occurs by 10-12 months. According to one view, it depends on experiential effects on psychoacoustic mechanisms. Alternatively, phonological development has been held responsible, with perception influenced by whether the nonnative sounds occur allophonically in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
443
2
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(470 citation statements)
references
References 42 publications
19
443
2
6
Order By: Relevance
“…This extends previous studies of second language acquisition which have shown a loss of plasticity with age: the later a language is learnt, the less proficient people are (Oyama, 1976;Flege et al, 1995): it now seems that even early exposure (during the most sensitive period) is not sufficient. After exposure to Spanish leads to the formation of one [e] category, it appears to be difficult for the brain to learn two new phonetic categories which overlap with this one (see also Best et al, 1988). Similarly, Catalan-born subjects who have first learned the two categories of their language apparently did not learn a third category when exposed to Spanish.…”
Section: Resultsmentioning
confidence: 99%
“…This extends previous studies of second language acquisition which have shown a loss of plasticity with age: the later a language is learnt, the less proficient people are (Oyama, 1976;Flege et al, 1995): it now seems that even early exposure (during the most sensitive period) is not sufficient. After exposure to Spanish leads to the formation of one [e] category, it appears to be difficult for the brain to learn two new phonetic categories which overlap with this one (see also Best et al, 1988). Similarly, Catalan-born subjects who have first learned the two categories of their language apparently did not learn a third category when exposed to Spanish.…”
Section: Resultsmentioning
confidence: 99%
“…Two classic models that have been widely used to explain these perception effects in second language learning rely on relationships between categories in the first language (L1) and second language (L2) to predict which are easier or harder to acquire: Flege's Speech Learning Model (Flege, 1987) and Best's Perceptual Assimination Model (Best et al, 1988). Flege's model uses equivalence classification to explain why sounds in L2 that are similar to sounds in L1 will be difficult to both perceive and produce, whereas sounds that are considered new, or different from any classes in the L1, will be easier to process.…”
Section: Extensions and Future Directionsmentioning
confidence: 99%
“…To assess these skills in infant CI users, we have constructed a new research laboratory within the ENT Clinic at the Indiana University School of Medicine (IUSM) to assess the speech perception and language skills of deaf infants before implantation and at regular intervals following cochlear implantation. One of the procedures we have adapted for this research program is the visual habituation (VH) procedure, which has been used extensively for the past three decades to assess the linguistic skills of NH infants [11,53,54]. Our goals in this initial research were to: (1) validate VH with this population of deaf and hard-of-hearing infants, and (2) use VH to track and assess infants' attention to speech and measure their speech discrimination skills before and after receiving a cochlear implant.…”
Section: Assessing Speech Perception Skills Of Deaf Infants After Cocmentioning
confidence: 99%
“…The VH procedure has been used extensively over the years to assess NH infants' ability to discriminate speech contrasts [11,53]. In the standard implementation of VH, infants are first habituated to several trials of a repeating speech sound presented simultaneously with a visual display (e.g.…”
Section: Experiment: Visual Habituation Proceduresmentioning
confidence: 99%